The integration of immersive virtual reality in tertiary nursing and midwifery education: A scoping review. (August 2019) - Fealy, Shanna; Jones, Donovan; Hutton, Alison; Graham, Kristen; McNeill, Liz; Sweet, Linda; Hazelton, Michael
Abstract: Background: Immersive virtual reality is an advancing technology that has the potential to change the traditional pedagogical approaches to teaching tertiary nursing and midwifery students. The application of immersive virtual reality in nursing and midwifery education may be a novel, accessible method for information provision and skill acquisition, however little is known of the extent of immersive virtual reality technology integration into tertiary nursing and midwifery programs. Objectives: The purpose of this review is to identify the application and integration of immersive virtual reality within nursing and midwifery tertiary education programs. Design: A scoping review based on the Joanna Briggs Institute methodology for scoping reviews was undertaken. An a priori review protocol and eligibility criterion was developed with the protocol subject to review a posteriori following first round screening. An electronic search of ten databases was conducted in January 2018. Results: A total of n = 506 non-duplicate records were identified and subjected to level one and level two screening. The search strategy and screening process identified n = 2 articles that were quality checked and included for review. Conclusions: There is currently a paucity of quality published literature on the application and/or integration of immersive virtual reality into nursing and midwifery tertiary education. Immersive virtual reality has the potential to increase competence and confidence for students providing accessible and repeatable learning opportunities in a fail-safe environment. There is a need for educators to be involved in the conceptualisation, design, integration and research of immersive virtual reality technology into undergraduate nursing and midwifery programs.